Using a spatial growth model to provide evidence of agricultural spillovers between countries in the NEPAD CAADP Framework - Ulimwengu, John M.; Sanyal, Prabuddha (International Food Policy Research Institute, 2011)
The NEPAD Comprehensive Africa Agriculture Development Programme (CAADP) has been endorsed by African Heads of State and Governments as a vision for the restoration of agricultural growth, food security, and rural development in Africa. The program aims at stimulating agriculture-led development to alleviate poverty and hunger, and achieve sustainable food security. The creation of a union is often rationalized on grounds of moving the equilibrium toward the first best solution whenever independent policies generate spillovers. This arises as a common agenda can significantly reduce the scope of free-riding behavior among member countries. In addition, cross-border externalities arising out of higher levels of market integration entails countries to agree on policy coordination. Using a Spatial Durbin Model for panel data, the present study explores the extent and magnitude of agricultural production spillover that might validate the adoption of CAADP agenda among African countries, especially among Sub-Saharan African countries. Overall, our results suggest the presence of positive and significant agricultural production spillover. No evidence of beggar-thy-neighbor or negative spillover policies was found; on average, each country received 2.5 percent growth as a result of spillover. Finally, our results suggest that convergence dynamics is much stronger when spillover is accounted for which provides a rationale for a common agenda such as CAADP.